Possibilidades e limites da associação na estruturação de unidades locais de reciclagem: o caso da Associação Nora: Novo Osasco reciclando atitudes dos trabalhadores com materiais recicláveis - Souza, José Raimundo de (Universidade do Vale do Rio do Sinos, 2005)
The approach of this research is the actions that gather picker-garbages and, even in informality or legalized as associations, they are generally called as “recycling cooperatives”. But, for these picker-garbages, an association format gives a strong socioeconomic and cultural link, and also a flux of work and resources that happen between the structure of the economy in the enterprise and the personal and family economy. The hypothesis is that the association model represents a kind of organization that allows the beginning of the enterprise as an extension of each individual´s domestic unities, giving the possibility of legalization without forcing them to make a choice between their family and their work. This, instead of demanding an exclusive dedication, makes possible the joining between reproduction and production (subsistence ways), defined by a unique logic: of life’s broader reproduction
Keywords: empreendimento eco-solidário; associações; catador de papel; economia do trabalho; economia solidária; echo-solidary enterprises eco-solidário; piker garbage man; solidary economy; works economy; Ciências Sociais Aplicadas